(untitled) (Interdisciplinary Studies Journal, 2024)
This article presents the results of a theoretical research on School Geography in the schooling process and the importance of teaching Geography through geographical concepts, which supported a practical teaching activity. Understanding the importance of insertion and epistemological deepening in geography teaching practices, the text seeks, through theoretical reflections, the inclusion of the concept of Territory to investigate population dynamics in the formation of Brazilian territory in the classroom. Consequently, it presents the supervised internship experience developed in the High School of the Geography Teaching Degree course at the Federal University of Rio Grande – FURG. The concept of Territory presented aims to understand the concrete and functional relationships established between social groups and the Geographic Space, not limiting itself to this but also understanding it from cultural relationships and the plurality of Brazilian territory, given its peculiar characteristics in area size, ecosystemic, and cultural diversity. It was found that, from the teaching practice developed during the internship, it was possible to expand the students’ understanding of the very concept of territory and the territorial formation of Brazil, allowing discussion on the categories of population and territory, as well as contemporary migratory dynamics.